Political ecology : an integrative approach to geography and environment-development studies - Zimmerer, Karl S.; Bassett, Thomas J. (New York : The Guilford Press, 2003)
This volume offers a unique, integrative perspective on the political and ecological processes shaping landscapes and resource use across the global North and South. Twelve carefully selected case studies demonstrate how contemporary geographical theories and methods can contribute to understanding key environment-and-development issues and working toward effective policies. Topics addressed include water and biodiversity resources, urban and national resource planning, scientific concepts of resource management, and ideas of nature and conservation in the context of globalization. Giving particular attention to evolving conceptions of nature-society interaction and geographical scale, an introduction and conclusion by the editors provide a clear analytical focus for the volume and summarize important developments and debates in the field."--Jacket.
Includes bibliographical references (p. 291-295) and index.
Keywords: Political ecology